Palestinian Lives Matter: Racialising Israeli Settler-Colonialism. Issue 2 (November 2020) - Lentin, Ronit
Abstract : Against the background of recent developments in Israel's racial rule over the Palestinians, the Black Lives Matter protests, and in view of Israel's declared intention to annex occupied Palestinian territories, this article theorises Israel's permanent war against the Palestinians as first, state of exception, second, racial state, and third, settler-colony. The paper critiques the focus on ethnicity as an analytical frame by Israeli scholars and posits race as a key concept in analising Zionist settler-colonialism. It proposes that rather than being a solution to European antisemitism, Zionism adopted discourses of race approximating those expressed by antisemitic regimes. As the Black Lives Matter movement proliferates, the article concludes by proposing that Palestine and the question of Palestine are becoming a truly global issue.